(untitled) (The Review of Diabetic Studies, 2024)
Healthcare-associated infections (HAIs) remain a major threat to patient safety worldwide and continue to impose clinical, operational, and economic burdens on health systems. In Saudi Arabia, rapid expansion of healthcare infrastructure, high patient acuity, and frequent seasonal surges (e.g., Hajj/Umrah-related demand in some regions) increase the importance of robust infection prevention and control (IPC). This research paper examines infection control practices in Saudi hospitals with a focus on (i) levels of compliance with core IPC measures, (ii) common challenges that weaken implementation, and (iii) improvement strategies aligned with contemporary quality and safety frameworks. Using a structured narrative review approach combined with a practical assessment framework, the paper synthesizes evidence on hand hygiene, personal protective equipment (PPE), environmental cleaning, isolation precautions, device-associated infection prevention bundles, antimicrobial stewardship, and surveillance systems. Findings indicate that compliance is strongest when hospitals maintain visible leadership support, standardized protocols, continuous training, and active auditing with feedback. However, recurring barriers include workload pressure, variable competency across staff categories, inconsistency in auditing methods, gaps in data integration, infrastructure constraints, and cultural or behavioral factors affecting adherence. The paper proposes a multi-level improvement roadmap emphasizing leadership governance, safety culture, competency-based training, real-time monitoring, digital solutions, human factors engineering, and sustained antimicrobial stewardship. Finally, a practical implementation model is offered for Saudi hospitals to strengthen compliance, reduce HAI incidence, and improve readiness for emerging infectious threats.